Peningkatan Proses Pembelajaran Tematik Terpadu pada Tema 3 Menggunakan Pendekatan Scientific di Kelas 1 SDN 18 Air Tawar Selatan Padang - Reza, Julita; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to describe the improvement of integrated thematic learning processes with a scientific approach in class IV SDN 18 Air Tawar Selatan, Padang City. This type of research is classroom action research using qualitative and quantitative approaches. The techniques used are observation, tests, and non-test. The results of the observation of RPP in cycle 1 obtained an average of 83.31%, and cycle 2 gained an average of 97.22%. Aspects of students in the first cycle with a percentage of 81.35% increased in the second cycle to 96.42%. This proves the scientific approach can improve student learning processes.